2006
DOI: 10.1371/journal.pctr.0010005
|View full text |Cite
|
Sign up to set email alerts
|

RTS,S/AS02A Malaria Vaccine Does Not Induce Parasite CSP T Cell Epitope Selection and Reduces Multiplicity of Infection

Abstract: Objective:The candidate malaria vaccine RTS,S/AS02A is a recombinant protein containing part of the circumsporozoite protein (CSP) sequence of Plasmodium falciparum, linked to the hepatitis B surface antigen and formulated in the proprietary adjuvant system AS02A. In a recent trial conducted in children younger than age five in southern Mozambique, the vaccine demonstrated significant and sustained efficacy against both infection and clinical disease. In a follow-up study to the main trial, breakthrough infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 28 publications
(55 reference statements)
3
70
0
Order By: Relevance
“…The vaccine, Engerix-B TM , targets the hepatitis B protection in children was found not to be strain specific and reduced multiplicity of infection. 58 Importantly, over the 45 month period of surveillance, RTS,S/AS02 A had an acceptable safety profile, with significantly less serious adverse events and a trend towards reduced all cause mortality compared to recipients of control vaccine.…”
Section: From Early Cs-based Vaccines To Rtssmentioning
confidence: 93%
“…The vaccine, Engerix-B TM , targets the hepatitis B protection in children was found not to be strain specific and reduced multiplicity of infection. 58 Importantly, over the 45 month period of surveillance, RTS,S/AS02 A had an acceptable safety profile, with significantly less serious adverse events and a trend towards reduced all cause mortality compared to recipients of control vaccine.…”
Section: From Early Cs-based Vaccines To Rtssmentioning
confidence: 93%
“…The synthetic peptide combination SPf66 that contains a short sequence from near the N terminus of the P. falciparum merozoite surface protein 1 (MSP1) was tested in The Gambia (91), and the recombinant protein-based RTS,S/AS02A that contains a large portion of the P. falcipa- VOL. 20, 2007 MOLECULAR EPIDEMIOLOGY OF MALARIA 197 on May 12, 2018 by guest http://cmr.asm.org/ rum circumsporozoite protein was tested in The Gambia (3) and Mozambique (69). The RTS,S/AS02A vaccine had a significantly protective effect and the SPf66 vaccine did not, but neither affected the allele frequencies of their respective antigens in the infections that occurred in the vaccine group compared to the control group (3,69,91).…”
Section: Vaccine Trialsmentioning
confidence: 99%
“…20, 2007 MOLECULAR EPIDEMIOLOGY OF MALARIA 197 on May 12, 2018 by guest http://cmr.asm.org/ rum circumsporozoite protein was tested in The Gambia (3) and Mozambique (69). The RTS,S/AS02A vaccine had a significantly protective effect and the SPf66 vaccine did not, but neither affected the allele frequencies of their respective antigens in the infections that occurred in the vaccine group compared to the control group (3,69,91). In contrast, a smaller trial in Papua New Guinea of a combination vaccine that included one allelic form of MSP2 showed that subjects who were vaccinated had subsequent P. falciparum infections with disproportionately higher relative frequencies of the alternative MSP2 allelic type, suggesting that this vaccine had an allele-specific effect on MSP2 (84).…”
Section: Vaccine Trialsmentioning
confidence: 99%
“…Because CSP is polymorphic, an obvious question was whether diversity in CSP may explain the partial efficacy of the RTS,S vaccine. Analyses of infecting genotypes in one phase II trial of RTS,S suggested that this was not the case as there was no evidence of selection for infections containing non-vaccine genotypes among vaccinated versus control subjects [197,198]. These findings highlight that although antigen polymorphism needs to be considered in vaccine development, it may not be a major issue for all vaccines.…”
Section: Vaccine Trials and Antigen Polymorphismmentioning
confidence: 98%